2(5x-1)+(-5x-3)=15

Simple and best practice solution for 2(5x-1)+(-5x-3)=15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5x-1)+(-5x-3)=15 equation:


Simplifying
2(5x + -1) + (-5x + -3) = 15

Reorder the terms:
2(-1 + 5x) + (-5x + -3) = 15
(-1 * 2 + 5x * 2) + (-5x + -3) = 15
(-2 + 10x) + (-5x + -3) = 15

Reorder the terms:
-2 + 10x + (-3 + -5x) = 15

Remove parenthesis around (-3 + -5x)
-2 + 10x + -3 + -5x = 15

Reorder the terms:
-2 + -3 + 10x + -5x = 15

Combine like terms: -2 + -3 = -5
-5 + 10x + -5x = 15

Combine like terms: 10x + -5x = 5x
-5 + 5x = 15

Solving
-5 + 5x = 15

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 5x = 15 + 5

Combine like terms: -5 + 5 = 0
0 + 5x = 15 + 5
5x = 15 + 5

Combine like terms: 15 + 5 = 20
5x = 20

Divide each side by '5'.
x = 4

Simplifying
x = 4

See similar equations:

| 5n^5+2n^3+11n^4=0 | | 10x=45-5 | | 15j+2=14 | | 5n^5+2n^3=-11n^4 | | 3(3+x)=x+15 | | x^3+3=x+15 | | 0.75(2x+6)-3=3(x+3) | | 3+x^3=x+15 | | .25p+10=.33p | | 5x^2+7x-22=0 | | 2(6-2a)=-15a+34 | | -6-3t+9-(-6t)-2t= | | t+(-7t)+(-4)-3t-(-1)= | | 1/3(m-6)+1/2(m+5)=5/3 | | 8t-(-t)+5+5t+9= | | 9n+115=12n+25 | | 4x+3=-7x+-1 | | p^2+25+5p=14p+1 | | 144=12x | | 1.4+1.6(t+6)=4.6 | | m^2-14m+40=0 | | 1b-7b= | | 12p+3=11 | | 205=12x+25 | | 181=12x+25 | | 4a-1a= | | 2p+18=-3p+40 | | 4a-a= | | 2(x-4)=5[r+(-7)] | | g-21=70 | | 3p+19=-2p+42 | | -3x+6=2x+4 |

Equations solver categories